The obligation to keep professional secrecy versus the obligation to report. (Legal journal - Research in Legal and Social Sciences, 2017)
The obligation to keep professional secrecy has always represented a dilemma that is more ethical than legal, in its confrontation with the duty to report acts punishable by public criminal action. For this reason, the principles of law, ethics and logic are taken into consideration to configure the cause of justification that acts as a scale between both obligations, yielding one with respect to the other before the weighting of legal rights at stake.
Keywords: Professional secrecy; Obligation to repor; Confrontation; Cause of justification; Legal goods